2018
DOI: 10.2514/1.c034275
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Noise Emission Model Accounting for Aircraft Flight Parameters

Abstract: Today's aircraft noise calculation programs either use simple sound source descriptions with few input parameters or highly sophisticated models with input parameters, which are difficult to obtain. To fill the gap between these two approaches, an aircraft noise emission model based on regression of measured noise with aircraft flight parameters is presented. To find a reasonable compromise between the degree of detail and number of required flight parameters, an extensive data exploration was conducted. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…The sound source database was developed for fast calculations using the sound emission model described in [32], which predicts the sound emission of turbofan powered aircraft as a function of the flight configuration (power setting, Mach number and aeroplane configuration, i.e., flaps, slats and landing gear). The database consists of two look-up tables for airframe and engine noise sources, where the sound emission levels are stored as a function of frequency, directivity and flight parameters.…”
Section: Noise Assessment Of System Scenarios (Level 3)mentioning
confidence: 99%
“…The sound source database was developed for fast calculations using the sound emission model described in [32], which predicts the sound emission of turbofan powered aircraft as a function of the flight configuration (power setting, Mach number and aeroplane configuration, i.e., flaps, slats and landing gear). The database consists of two look-up tables for airframe and engine noise sources, where the sound emission levels are stored as a function of frequency, directivity and flight parameters.…”
Section: Noise Assessment Of System Scenarios (Level 3)mentioning
confidence: 99%
“…3 The individual technologies and components are provided from the component level (based on their high-fidelity simulation results), transferred to the single aircraft level (here the technologies and components are installed on an aircraft and the overall noise immission is predicted), to finally integrate the new vehicles into a scenario (the overall noise immission around the airport is predicted according to the scenario, see Ref. 61 ). Obviously, it was necessary to combine various simulation tools of strongly different fidelity levels in order to enable this overall assessment.…”
Section: "Toward a Fully Automated Low-noise Design Process" (2009-2012)mentioning
confidence: 99%
“…After determining the noise levels from these tables for a specific observer position, corrections such as lateral attenuation, segment event level corrections, installation effects, and bank angle effects may apply. Previous comparisons between aircraft noise prediction models and experimental measurements [3,4] showed that considerable errors are made by the models due to the large assumptions considered within their calculations. Therefore, experimental validations and potential improvements of these models are highly recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Other more sophisticated, semi-empirical prediction models, such as ANOPP [5], PANAM [6] or SIMUL [7] describe the sound emission and propagation separately and offer more detailed predictions but they require very detailed input data, which are not typically publicly available and their database is limited to a small number of aircraft [4]. In addition, these programs are not accessible to other users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation